(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
Starting from a case study (“I vampiri”) the contribution aims to revise the framework and identity of the modes of production of the period. The progenitor of Italian horror is read as an embodiment of relationships, processes and practices reflecting the transformations taking place in other economic-industrial fields. The investigation into the production practices of the different versions of the film leads to different historical-economic phenomena and processes, pointed to in Freda and Bava’s film both through microscopic details and marginal clues, and its belonging to a context intent on rewriting production chains and processes on a transnational scale.